Globalizing the Balkans. Balkan Studies as a Transnational/Translational Paradigm - Blažević, Zrinka (2009)
Starting from the premise that space is both a physical givenness and a social construct, the main focus of this paper will be placed upon an alternative theoretical conceptualization of the Balkans as a possible heuristic framework for rethinking and epistemological broadening of the Balkans Studies. Drawing upon Michel Foucault’s concept of heterotopia as "impossible space" of coexistence of the opposite, distinctive and incommensurable, I will propose a conceptualization of the Balkans as a heterotopical space in geographical, historical, social, political, cultural and symbolic terms. Accordingly, it will be argued that such a conceptualization might provide a basis for a transnational and translational politics of the discipline which could not only bring about useful heuristic models and research protocols for future Balkan Studies, but also ensure a survival of this academic and research field in the post-transitional, global age.